Understanding the Bacterial Response to Mycotoxins: The Transcriptomic Analysis of Deoxynivalenol-Induced Changes in Devosia mutans 17-2-E-8 - Hassan, Yousef I.; He, Jian Wei; Lepp, Dion; Zhou, Ting (Frontiers in Pharmacology, 2019)
Deoxynivalenol (DON) is a major fusarium toxin widely detected in cereal grains. The inadvertent exposure to this fungal secondary-metabolite gives rise to myriad adverse health effects including appetite-loss, emesis, and suppression of the immune system. While most of the attention to this mycotoxin has gained in the past four decades is related to its eukaryotic toxicity (monogastric-animals and plants more precisely), recent studies have begun to reveal its negative influence on prokaryotes. Recent evidence indicates that DON can negatively affect many bacterial species, raising the possibility of DON-induced imbalances within the microbiota of the human and animal gut, in addition to other environmental niches. This in turn has led to a greater interest in understanding bacterial responses towards DON, and the involved mechanisms and metabolic pathways, to build a more comprehensive picture of DON-induced changes in both prokaryotes and eukaryotes. This study reveals the transcriptomic profiling of Devosia mutans strain 17-2-E-8 after the inclusion of DON within its growth medium. The results highlight three adaptive mechanisms involved in the response of D. mutans 17-2-E-8 to this mycotoxin, which include: (a) ATP-binding cassette (ABC) transporters; (b) a toxin-specific pyrroloquinoline quinone (PQQ)-dependent detoxification pathway; and finally (c) the upregulation of auxiliary coping proteins such as porins, glutathione S-transferases, and phosphotransferase. Some of the identified mechanisms are universal in nature and shared with other bacterial genera and species.